2016
DOI: 10.1039/c5en00253b
|View full text |Cite
|
Sign up to set email alerts
|

The effects of recycling on the properties of carbon nanotube-filled polypropylene composites and worker exposures

Abstract: With production of nanocomposites, the product life cycle, including recycling, becomes critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 53 publications
0
22
1
2
Order By: Relevance
“…The authors found that, by increasing the number of cycles, the filled polymers were more sensitive to the higher shear stress involved during the injection processing. This is in contrast with the results of an earlier investigation carried out by the authors [36] on CNT-filled PP in which neat PP was found less resistant to degradation than the corresponding CNT-PP composites. Figure 10 shows a continuous decrease in the values of flexural modulus for the reprocessed PP, resulting from polymer matrix degradation during reprocessing [1][2][3][4][5].…”
Section: Mechanical Testscontrasting
confidence: 99%
“…The authors found that, by increasing the number of cycles, the filled polymers were more sensitive to the higher shear stress involved during the injection processing. This is in contrast with the results of an earlier investigation carried out by the authors [36] on CNT-filled PP in which neat PP was found less resistant to degradation than the corresponding CNT-PP composites. Figure 10 shows a continuous decrease in the values of flexural modulus for the reprocessed PP, resulting from polymer matrix degradation during reprocessing [1][2][3][4][5].…”
Section: Mechanical Testscontrasting
confidence: 99%
“…Zhang et al (88) studied the effects of recycling on the properties of carbon nanotube filled polypropylene nanocomposites. They found that the CNT-filled PP materials showed an increase in toughness with recycling ( Figure 19).…”
Section: Recyclability Of Pp-based Nanocompositesmentioning
confidence: 99%
“…It should be pointed out that the behaviors for other nanofilled materials can be quite different and will be dependent on the base polymer. For example, CNT‐filled polypropylene exhibits greater resistance to degradation as compared to the neat polypropylene, while in contrast there is greater susceptibility to degradation shown by the CNT‐filled PC as compared to neat PC . Thus, the effect of nanoscale fillers on the recycling behavior is highly dependent on the specific polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the degree of dispersion could potentially increase with the additional processing steps in recycling, which could yield improved properties. Our previous study about the effect of recycling on CNT‐filled Polypropylene (PP) showed that CNT‐filled PP had higher resistance to recycling compared to neat PP due to improved crystallization behavior with recycling . Thus, nanocomposites can show improved properties with recycling as opposed to degradation in properties.…”
Section: Introductionmentioning
confidence: 99%